Hambatan Pemberian ASI Eksklusif Pada Bayi Usia 0-6 Bulan - Asnidawati Asnidawati; Syahrul Ramdhan (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Abstract. Introduction; the rate of exclusive breastfeeding has been made by various international and national efforts, however, the coverage rate for exclusive breastfeeding has not reached the predetermined target. know the causes or barriers to exclusive breastfeeding in infants aged 0-6 months. Method; data were obtained from various electronic databases using google scholar, scientific director, and published using the keywords "infant feeding, exclusive breastfeeding, resistance". Result; that many factors inhibit mothers in giving exclusive breastfeeding to infants aged 0-6 months, namely health factors and health facilities, poor perceptions of breastfeeding, sociodemography, knowledge of breastfeeding, socio-culture, and environment. health workers plan tips to support mothers in maintaining maternal success in exclusive breastfeeding